HISTORY OF GREAT BRITAIN (Ustozlar uchun, 2026)
This article examines the historical development of Great Britain from prehistoric times to the modern era. It analyses the principal political, economic, social, and cultural transformations that shaped the British state, including the Roman conquest, Anglo-Saxon settlement, Norman rule, the formation of parliamentary institutions, the Industrial Revolution, imperial expansion, and the post-imperial transition. Drawing on a broad body of scholarship, the study highlights how internal dynamics and external pressures jointly produced the distinctive trajectory of British history. The article integrates political, economic, and social perspectives to provide a balanced, scholarly synthesis suitable for advanced study and research.